Porous nanoapatite scaffolds synthesized using an approach of interfacial mineralization reaction and their bioactivity. Issue 8 (1st April 2014) - Wang, Jianxin; Yan, Haoran; Chen, Taijun; Wang, Yingying; Li, Huiyong; Zhi, Wei; Feng, Bo; Weng, Jie; Zhu, Minghua
Abstract There is a growing interest in the use of calcium phosphate, used to fabricate porous scaffolds for bone tissue regeneration and repair. However, it is difficult to obtain interconnected pores with very high porosity and to engineer the topography of the pore walls for calcium phosphate ceramic scaffolds. In this study, a novelty method interfacial mineralization reaction was used to fabricate porous nano‐calcium phosphate ceramic scaffolds with three‐dimensional surface topography of walls, which was tuned using different surfactants; using this method, porous scaffolds with different shapes were obtained, which demonstrates that interfacial mineralization reaction is not only a good method to prepare porous ceramic scaffolds of calcium phosphate but also an efficient approach to engineer the topography of the pore walls. The as‐prepared porous ceramic scaffolds have also been proved to have good biocompatibility, bioactivity, and biodegradability, which are necessary for the clinical application. In vivo experimental results revealed that not only osteoconduction but also osteoinduction was responsible for the bone formation in our scaffolds, which accelerated the formation of new bone, and that the degradation process of our porous scaffolds could match osteoinduction, mineralization of matrix and bone, and reconstruction of new bone very well, and porous scaffolds could be completely substituted by the new bone. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1749–1761, 2014.